OPTIMIZATION OF NATIONAL STRATEGIC LEADERSHIP/TNI IN ACCELERATION OF COVID-19 HANDLING AND NATIONAL ECONOMIC RECOVERY FROM DEFENSE ECONOMIC PERSPECTIVE - Juliana Juliana; Guntur Eko Saputro; Susilo Adi Purwanto (Bajang Institute, 2022)
Indonesia is currently facing the same problem, namely the COVID-19 pandemic. As a result of the COVID-19 pandemic in Indonesia, it has had a major impact on various sectors, one of which is in terms of the economy. The Indonesian government has made every effort to accelerate the handling of Covid-19 and restore the national economy. In accelerating the handling of Covid-19 and recovering the national economy, a strategic leadership figure is needed, namely the national leadership/TNI. In an effort to realize the optimization of the national strategic leadership/TNI in accelerating the handling of Covid-19 and the current national economic recovery, there are several obstacles, including limited planning capabilities, limited ability to implement strategies and limited evaluation capabilities. This research focuses on national/TNI strategic leadership. The methodology used is a descriptive qualitative research method through a literature study approach. The research uses optimization theory, strategic leadership and human resource management to analyze this study. The results of the analysis show that the optimization of the national strategic leadership/TNI is manifested in a number of fields such as the health sector, the social-economic sector and the security sector in an effort to accelerate the handling of COVID-19 and the national economic recovery